2018
DOI: 10.1111/jcmm.13552
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin mediated pro‐angiogenic role of Hydroxysafflor Yellow A in ischaemic cardiac dysfunction: Post‐transcriptional regulation of VEGF‐A and MMP‐9

Abstract: Hydroxysafflor Yellow A (HSYA), a most representative ingredient of Carthamus tinctorius L., had long been used in treating ischaemic cardiovascular diseases in China and exhibited prominently anticoagulant and pro‐angiogenic activities, but the underlying mechanisms remained largely unknown. This study aimed to further elucidate the pro‐angiogenic effect and mechanism of HSYA on ischaemic cardiac dysfunction. A C57 mouse model of acute myocardial infarction (AMI) was firstly established, and 25 mg/kg HSYA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…Therefore, the changes of VEGF-A content, angiogenesis, ER stress, and autophagy in the endothelial cells of ischemic myocardium in the AMI mice were first determined, and then in vitro studies were performed to analyze the role of ER stress and autophagy in VEGF-Ainduced angiogenesis and the potential mechanisms. A mouse model of AMI was established by occlusion of the left anterior descending coronary artery according to the procedure we previously reported (Zou et al, 2018).…”
mentioning
confidence: 99%
“…Therefore, the changes of VEGF-A content, angiogenesis, ER stress, and autophagy in the endothelial cells of ischemic myocardium in the AMI mice were first determined, and then in vitro studies were performed to analyze the role of ER stress and autophagy in VEGF-Ainduced angiogenesis and the potential mechanisms. A mouse model of AMI was established by occlusion of the left anterior descending coronary artery according to the procedure we previously reported (Zou et al, 2018).…”
mentioning
confidence: 99%
“…It was confirmed that SYA could protect neonatal rat cardiomyocytes against anoxia/reoxygenation injury in vitro [34]. There have been a large number of studies showing the protective effects of HSYA on the cardiovascular system [35][36][37], nervous system [38,39], liver [40,41], lung [42,43], and others. It was also found to inhibit certain tumors [44,45] and has a certain impact on metabolism [46].…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, cells with high glucose showed no signi cant changes compared to control group, illustrating the non-cytotoxic effect of 30 mM glucose concentration. The initial process of angiogenesis is the organization of individual endothelial cells into a 3-dimensional tube-like structure [51]. RAECs were seeded on the basement membrane matrix.…”
Section: L-arginine and Vitamin C Enhanced Angiogenesis In Raecsmentioning
confidence: 99%